Tweets and the Streets Social Media and Contemporary Activism - Gerbaudo, Paolo (Pluto Press, 2012)
Tweets and the Streets analyses the culture of the new protest movements of the 21st century. From the Arab Spring to the 'indignados' protests in Spain and the Occupy movement, Paolo Gerbaudo examines the relationship between the rise of social media and the emergence of new forms of protest. Gerbaudo argues that activists' use of Twitter and Facebook does not fit with the image of a 'cyberspace' detached from physical reality. Instead, social media is used as part of a project of re-appropriation of public space, which involves the assembling of different groups around 'occupied' places such as Cairo's Tahrir Square or New York's Zuccotti Park. An exciting and invigorating journey through the new politics of dissent, Tweets and the Streets points both to the creative possibilities and to the risks of political evanescence which new media brings to the contemporary protest experience.